Blood Pressure Control 1 Year After Referral to a Hypertension Specialist. Issue 9 (17th June 2013) - Denker, Matthew G.; Haddad, Danny B.; Townsend, Raymond R.; Cohen, Debbie L.
Abstract : Hypertension is highly prevalent and remains poorly controlled. The purpose of this study was to evaluate blood pressure (BP) control in patients with uncontrolled hypertension 1 year after referral to a hypertension specialist. A retrospective chart review was performed on 158 patients evaluated by a single hypertension specialist between 2005 and 2010 at the Penn Hypertension Program. Patients were included if they had at least 1 year of follow‐up and had baseline plasma renin activity and plasma aldosterone concentration measured. Drug regimens were adjusted with particular attention to results of renin‐aldosterone profiling. Mean BP of the entire cohort decreased from 149/87 mm Hg to 129/78 mm Hg at 1 year ( P <.0001), without a significant change in the number of antihypertensive medications. The authors observed that referral to a hypertension specialist was worthwhile and associated with a significant reduction in BP without an increase in the number of BP medications used at 1 year.